Reformar educacionais nos anos noventa no estado de Minas Gerais: o projeto Proqualidade - Fonseca, Aparecida Maria (2006)
The present study fits into the Line of Educational Policies and Management of the Post Graduate Program in Education of the Federal University of Uberlândia, and its central theme is to investigate the scope, assimilation, conflicts and resistances in the process of implementing the pro-quality program Programa Proqualidade within the public school, which was implemented in the teaching system of the State of Minas Gerais, between the years 1994 and 1999. The broad aim was to analyze the implications for the pro-quality program within the Minas Gerais State public school, from the perspective of three of the five priorities of the program: School Autonomy, Strengthening the Board, Qualification, Improvement and Assessment. The intention furthermore, was to understand the changes that occurred in the educational policies in Minas Gerais, within the context of the neoliberal State reform; analyze the pro-quality program from the nexus and interfaces with the changes in the workday world and state the problems of the implications and outlines of educational reforms in Minas Gerais in the 1990s, inside the school, from the perspective of the proquality program. To achieve these objectives, the effectuation of the Neoliberal State was discussed, as from the 1970s, perceiving its characteristics and the possible mediations between the neoliberal policies and education; total Quality Management and the transformations in the workday world, seeking to approach the technological, organizational and managerial innovations that impacted on the production sector and also on the school. Furthermore, through empirical study, it was sought to learn of the perceptions of school subjects with regard to the theme under analysis. As regards the methodological aspect, this study fits into the field of qualitative research, because it is believed that conducting research in this field enables the researcher to construct and overall and articulated view of the investigated object and its relation with political and economic aspects. The institution investigated forms part of the state public teaching network situated in the municipality of Uberlândia/MG, Brazil and serves the basic and middle teaching levels. In the data collection process, the instrument used was the semi-structured interview, and analysis of school documents, such as: collegiate minutes, correspondence sent to the company, videos and others. In the final considerations, it was concluded that the educational reform of the proquality program ( Programa Proqualidade ) for school autonomy attributed responsibilities that previously were the State s to the school, but without providing conditions for the subjects of education to be in a position to work, because the resources continued to be insufficient to fill all the needs in this space, while at the same time it assessed the school for good work. This being so, the professionals resisted at various times, but without being in a position to deny a program based on the search for quality. In spite of this, the reform for quality did not achieve the object, as educators wished; educators tried to construct their autonomy by articulating political, professional and pedagogic interests: but the school must extrapolate the rules and regulations and make use of the space that is granted to it to seek solutions compatible with its difficulties. It is necessary for education to be participative, transformational and revolutionary.